Association between maternal single nucleotide polymorphisms in genes regulating glucose metabolism and risk for neural tube defects in offspring. Issue 6 (5th November 2014) - Fu, Yunting; Wang, Lin‐lin; Yi, Deqing; Jin, Lei; Liu, Jufen; Zhang, Yali; Ren, Aiguo
Abstract : Background: Maternal pregestational hyperglycemia, diabetes, and obesity are well‐established risk factors for neural tube defects (NTDs). As a common underlying mechanism, the imbalance of glucose homeostasis is directly related to the development of NTDs. Polymorphisms in genes regulating glucose metabolism in women may impact their chance of having an NTD‐affected pregnancy. Methods: We conducted a two‐stage case‐control study to investigate the association between maternal genetic variants in genes regulating glucose metabolism and risk for NTDs. The cases were 547 women who gave birth to a child with an NTD (anencephaly, spina bifida, or encephalocele); the controls were 543 women who gave birth to a full‐term healthy infant. In the first stage, 12 single nucleotide polymorphisms were genotyped in 160 cases and 162 controls. In the second stage, five single nucleotide polymorphisms found in the first stage and potentially associated with NTD risk were genotyped for validation, in an additional 387 cases and 381 controls. Results: Combined analysis of data from the two stages showed an association between maternal AA genotype of GCKR rs780094 and increased risk for total NTDs [odds ratio, 1.73; 95% confidence interval, 1.16–2.59) and spina bifida subtype [odds ratio, 1.83; 95% confidence interval, 1.16–2.88). No association was found between the other four single nucleotide polymorphisms ( LEPR rs1137100, HK1 rs748235, HHEX rs5015480, KCNQ1 rs2237892) and NTD risk. Conclusion: The AA genotype in maternal GCKR rs780094 is associated with an increased risk for NTDs and spina bifida in the Chinese population. Birth Defects Research (Part A) 103:471–478, 2015. © 2014 Wiley Periodicals, Inc.